Assembly of Gold Nanoparticles on Gold Nanorods Using Functionalized Poly(N‐isopropylacrylamide) as Polymeric "Glue". (9th June 2016) - Fan, Ziyin; Tebbe, Moritz; Fery, Andreas; Agarwal, Seema; Greiner, Andreas
Abstract : A telechelic thermoresponsive polymer, α ‐amino‐ ω ‐thiol‐poly( N ‐isopropylacrylamide) (H2 N‐PNiPAM‐SH), is used as the polymeric glue to assemble gold nanoparticles (AuNPs) around gold nanorods (AuNRs) into a satellite structure. Prepared by reversible addition‐fragmentation chain transfer polymerization followed by hydrazinolysis, H2 N‐PNiPAM‐SH is able to interlink the two types of the gold building blocks with the thiol‐end grafting on AuNRs and the amine‐end coordinating on the AuNP surface. The density of the grafted AuNPs on AuNRs can be tuned by adjusting the molar ratio between AuNPs and AuNRs in the feed. The resulted satellite‐like assembly exhibits unique optical property that was responsive to temperature change. Abstract : Self‐assembly of gold nanoparticles around gold nanorods is prepared by using functionalized poly( N ‐isopropylacrylamide) as polymer "glue." The resulting nanomaterial shows certain thermoresponsive behavior. The grafting density of gold nanoparticles on the surface of gold nanorods is fine‐tuned by adjusting the molar ratio between gold nanoparticles and nanorods in feed.